miR-1246 in tumor extracellular vesicles promotes metastasis via increased tumor cell adhesion and endothelial cell barrier destruction - Morimoto, Masahiro; Maishi, Nako; Tsumita, Takuya; Alam, Mohammad Towfik; Kikuchi, Hiroshi; Hida, Yasuhiro; Yoshioka, Yusuke; Ochiya, Takahiro; Annan, Dorcas A.; Takeda, Ryo; Kitagawa, Yoshimasa; Hida, Kyoko (Frontiers in Oncology, 2023)
Abstract Background: Tumor blood vessels play a key role in tumor metastasis. We have previously reported that tumor endothelial cells (TECs) exhibit abnormalities compared to normal endothelial cells. However, it is unclear how TECs acquire these abnormalities. Tumor cells secrete extracellular vesicles (EVs) to create a suitable environment for themselves. We have previously identified miR-1246 to be more abundant in high metastatic melanoma EVs than in low metastatic melanoma EVs. In the current study, we focused on miR-1246 as primarily responsible for acquiring abnormalities in TECs and examined whether the alteration of endothelial cell (EC) character by miR-1246 promotes cancer metastasis. Methods: We analyzed the effect of miR-1246 in metastatic melanoma, A375SM-EVs, in vivo metastasis. The role of tumor EV-miR-1246 in the adhesion between ECs and tumor cells and the EC barrier was addressed. Changes in the expression of adhesion molecule and endothelial permeability were examined. Results: Intravenous administration of A375SM-EVs induced tumor cell colonization in the lung resulting in lung metastasis. In contrast, miR-1246 knockdown in A375SM decreased lung metastasis in vivo. miR-1246 transfection in ECs increased the expression of adhesion molecule ICAM-1 via activation of STAT3, followed by increased tumor cell adhesion to ECs. Furthermore, the expression of VE-Cadherin was downregulated in miR-1246 overexpressed EC. A375SM-EV treatment enhanced endothelial permeability. VE-Cadherin was validated as the potential target gene of miR-1246 via the target gene prediction database and 3′ UTR assay. Conclusion: miR-1246 in high metastatic tumor EVs promotes lung metastasis by inducing the adhesion of tumor cells to ECs and destroying the EC barrier.